2010
DOI: 10.1111/j.1471-4159.2010.06887.x
|View full text |Cite
|
Sign up to set email alerts
|

ABCG2 reduces ROS‐mediated toxicity and inflammation: a potential role in Alzheimer’s disease

Abstract: J. Neurochem. (2010) 114, 1590–1604. Abstract Alzheimer’s disease is characterized by accumulation and deposition of Aβ peptides in the brain. Aβ deposition generates reactive‐oxygen species (ROS), which are involved in Alzheimer’s inflammatory and neurodegenerative pathology. We have previously observed that, in Alzheimer’s disease brain, ABCG2 is up‐regulated and AP‐1 is activated, but NF‐κB is not activated. In the present study, we examine the roles and mechanism of ABCG2 on ROS generation, inflammatory ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
71
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(77 citation statements)
references
References 56 publications
4
71
1
1
Order By: Relevance
“…This result was further confirmed in vitro in N2a-695 cells where overexpression of ABCG2 significantly decreased the processing rate of APP and Aβ production as compared with controls. 126 Lack of difference in ABCG2 expression in the brain vasculature of AD compared to normal cases has also been reported. 59 While further studies are necessary to confirm these results, this discrepancy could be related to regional variations, for example, hippocampal 59 vs occipital cortical 124 regions, in the extent of ABCG2 vascular changes in AD.…”
Section: ■ Abcg Family Abcg2 (Breast Cancer Resistance Protein Bcrp)mentioning
confidence: 95%
“…This result was further confirmed in vitro in N2a-695 cells where overexpression of ABCG2 significantly decreased the processing rate of APP and Aβ production as compared with controls. 126 Lack of difference in ABCG2 expression in the brain vasculature of AD compared to normal cases has also been reported. 59 While further studies are necessary to confirm these results, this discrepancy could be related to regional variations, for example, hippocampal 59 vs occipital cortical 124 regions, in the extent of ABCG2 vascular changes in AD.…”
Section: ■ Abcg Family Abcg2 (Breast Cancer Resistance Protein Bcrp)mentioning
confidence: 95%
“…Although the role of this protein in zebrafish is still unknown, S100 proteins are endogenous activators of innate immune responses in mammals, and some of them have proinflammatory properties and are associated with different inflammatory diseases, such as inflammatory bowel disease. [82][83][84] Several genes involved in the relief of oxidative stress as a compensatory mechanism were up-modulated in tolerized zebrafish as described for mammals 85,86 ; these include glutathione peroxidase 7 (GPX7), which mitigates the organ dysfunction during chronic inflammation, and phosphoenolpyruvate synthase, which is an essential enzyme when pyruvate and lactate are used as a carbon source. The upmodulation in tolerized fish suggests a mechanism for avoiding the excess of lactate and hypoxia that induces the organ failure associated with sepsis.…”
Section: Transcriptome In Lps Tolerancementioning
confidence: 99%
“…In fact, it was reported that ABCG2 may relieve oxidative stress and inflammatory response in brain tissues and may play a protective role in Alzheimer disease. 11 In the heart, we previously demonstrated that ABCG2 is expressed mainly in endothelial cells of mi-crovessels and plays a pivotal role in cardiac repair after myocardial infarction by promoting angiogenesis. 12 These findings suggest that ABCG2 may be important for tissue defense in various diseases.…”
Section: See Accompanying Article On Page 545mentioning
confidence: 99%